ANALISIS FAKTOR YANG MEMPENGARUHI LOYALITAS MEREK DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Amara Prameswari, Arnintya; Santosa, Suryono Budi (Diponegoro Journal of Management, 2021)
Communication tool is one of the needs that is not less important in human life. One type of communication tool that is often used at this time is a smartphone. As a form of realizing brand loyalty, there are several factors that influence customer loyalty to a particular brand, such as perceived quality, perceived value, brand identification, and lifestyle congruence related to these products. The purpose of this study was to analyze the effect of perceived quality, perceived value, brand identification, and lifestyle congruence on brand loyalty with customer satisfaction as an intervening variable. This research was conducted for residents residing in Semarang. The number of samples in this study were 152 respondents with the criteria being using an iPhone or having used an iPhone before. The data collection method used in this study is through a questionnaire. This study uses Structural Equation Modeling (SEM) as an analytical tool. The results of this study indicate that perceived quality has a positive and significant effect on customer satisfaction, perceived value has a positive and significant effect on customer satisfaction, brand identification has a positive and significant effect on customer satisfaction, and lifestyle congruence has a positive and significant effect on customer satisfaction. In addition, it is known that customer satisfaction is proven to mediate the relationship between perceived quality, perceived value, brand identification, and lifestyle congruence on brand loyalty.